Community Participation in Development: Case Study in Teba Village - Fahik, Yakobus; Mbiri, Adeodata Laniria C.B; Seran, Remigius (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
The focus of this research is on community participation. This focus is operated on the work program currently being carried out by Teba village: whether the work program implemented is the result of a decision of the village council forum or the village head’s own initiative. Using Arnstein’s participation ladder, we will analyze the level of community participation in development in Teba village, Biboki Tanpah District, North Central Timor Regency. Using the interview method and supported by documents in the form of village meeting minutes (musdes), village meeting attendance lists (musdes), and document work plan (RKPdes) from 2019- 2024, data collected and analyzed to determine the level of community participation. The study conducted found that community participation in Teba village was at the second level. At the information provision rung, the public is given information but the decision has been taken. Likewise, on the consultation ladder. The village head conducts discussions but, there is no guarantee the suggestions will be accepted. In taking heart, the government only makes promises that can easily be ignored.